The influence of variable vane angle air swirler on reducing emissions from combustion process - Mohd. Jaafar, Mohammad Nazri; Samat, Ismail; Abdul Mookmin, Muhamad Shukri (Faculty of Mechanical Engineering, 2002)
The effect of varying the vane angle on reducing emissions such as oxides of nitrogen (NOx) and carbon monoxide (CO) from combustion processes is presented. In this paper, a liquid fuel burner system with different radial air swirler vane angles has been investigated using 163 mm inside diameter combustor of 280 mm length. A radial flow air swirler with straight vanes having 40 mm outlet diameter was inserted at the inlet plane of the combustor to produce swirling flow. All tests were conducted using kerosene as fuel. Fuel was injected at the back plate of the swirler outlet using central fuel injector with two fuel nozzles pointing axially outwards. The swirler vane angles and equivalence ratios were varied. Tests were carried out using four different air swirlers having 30°, 40°, 50° and 60° vane angles, respectively. NOx reduction of more than 27 percent was obtained for the swirler with vane angle of 60° compared to 30° vane angle. CO emissions were also reduced by 38 percent for 60° vane angle compared 30° vane angle This was achieved at equivalence ratio of 0.95. This paper demonstrated that NOx emission decreases with increase in vane angle of radial air swirler.